Mathematical modelling for biomitigation of lead from waste water using packed-bed biofilm reactor. (1st December 2022) - Bose, Moumita
Abstract: A mathematical model was developed from first principle to predict the concentration distribution in the axial direction in a packed bed biofilm reactor used for the removal of lead from wastewater by bioremediation. The biocatalyst was prepared by immobilizing Acinetobacter sp . 158 (isolated in-house from a native source) on a sintered sticky Earthen sphere using an attached growth technique. To evaluate the intrinsic kineticparameters necessary for the simulation, batch mode studies of the same system were carried out, and the cell growth dynamics were established. It was observed that within the concentration of lead from 0.01 kg m −3 to 0.04 kg m −3 the system followed the Monods substrate uninhibited model equation. The first order differential equation obtained through thesteady-state mass balance in the axial direction of the packed bed contained no adjustable parameters, and the equation was solved analytically. Within the lead concentration range 0.01 kg m −3 −0.04 kg m −3 and flow velocity 1.43 m h −1 −5.73 m h −1 experimental data shows best alignment with the simulated values. The close fit of such experimental data with the simulated values indeed clearly indicates the validity of the proposed deterministic model equation.